Peran Serta Masyarakat dengan Angka Kejadian Diare - Nurhaedah Nurhaedah; Rahmat Pannyiwi; Suprapto Suprapto (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Diarrhea is one of the most common causes of child morbidity and mortality, exacerbated by inadequate water, sanitation and hygiene services, and malnutrition, especially in developing countries. Purpose: Knowing the participation of the community in the incidence of diarrhea. Methods: Quantitative research design using an observational analytical approach with Cross-Sectional. The total sample of 69 people, the collection of in-depth interview data, observation, and document review, were analyzed univariately and bivariate with the help of SPSS version 21. Results: This shows that the chi-square statistical test obtained a p-value = 0.000 < 0.05 for the role of society. Conclusion: There is a relationship between the part of society with the incidence of diarrhea. Therefore, in conducting socialization and education or counseling about the incidence of diarrhea to the entire community by collaborating with health workers to increase the community's active role in health.